Financial advisors: A case of babysitters? - Andreas Hackethal; Michael Haliassos; Tullio Jappelli (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
We merge administrative information from a large German discount brokerage firm with regional data to examine if financial advisors improve portfolio performance. Our data track accounts of 32,751 randomly selected individual customers over 66 months and allow direct comparison of performance across self-managed accounts and accounts run by, or in consultation with, independent financial advisors. In contrast to the picture painted by simple descriptive statistics, econometric analysis that corrects for the endogeneity of the choice of having a financial advisor suggests that advisors are associated with lower total and excess account returns, higher portfolio risk and probabilities of losses, and higher trading frequency and portfolio turnover relative to what account owners of given characteristics tend to achieve on their own. Regression analysis of who uses an IFA suggests that IFAs are matched with richer, older investors rather than with poorer, younger ones.
urn:nbn:de:hebis:30-63751
Keywords: G1; E2; D8; 330; Financial Advice; Portfolio Choice; Household Finance; Privater Haushalt; Portfolio-Management; Kapitalanlage; Anlageberatung; Kapitalertrag; Deutschland